Characteristics of gut microbiome in patients with pediatric solid tumor - Du, Xiaoran; Cui, Xu; Fan, Rongrong; Pan, Juntao; Cui, Xichun (Frontiers in Pediatrics, 2024)
Background: Pediatric solid tumors are a common malignant disease in children, and more and more studies have proved that there is an inseparable relationship between adult tumors and intestinal microbiome, but the changes in the intestinal microbiota of pediatric solid tumor (PST) patients have been scarcely examined. This study aims to examine the differences in the intestinal microbiota features between patients diagnosed with PST and healthy controls (HCs).Methods:To elucidate the unique characteristics of the gut microbiota in pediatric patients with solid tumors, we recruited 23 PST patients and 20 HCs. A total of 43 stool samples were gathered, and then 16S rRNA sequencing was performed.We noticed a noticeable pattern of elevated diversity in the gut microbiota within the PST groups. The differences in microbial communities among two groups were remarkable, regarding the analysis at the class level, the abundance of Bacilli was markedly increased in PST patients compared to HCs(P<0.05), regarding the analysis at the genus level, The presence of Enterococcus was significantly higher in PST cases compared to HCs(P<0.01), while Lachnospiraceae unclassified, Lachnospira, Haemophilus and Colidextribacter in PST cases, the abundance was significantly reduced. (P<0.05), 6 genera, including Bacilli, Lactobacillales, Enterococcaceae and Morganella, showed a significant enrichment compared to healthy controls, while 10 genera, including Bilophila, Colidextribacter, Pasteurellales, Haemophilus, Lachnospiraceae unclassified, Lachnospira and Fusobacteriales, were significant reduction in the PST groups.2 Conclusion: Our research conducted the characterization analysis of the gut microbiota in PST patients for the first time. More importantly, there are some notable differences in the gut microbiota between PST patients and healthy controls, which we believe is an interesting finding.Pediatric solid tumor (PST), healthy controls (HCs), 16S rRNA sequencing, microbial marker, gut microbiome